“Freemium” business models in publishing. New packaging for the needs of readers in the digital age (Libellarium: journal for research in the field of information and related sciences, 2015)
In a digital environment, the traditional roles of authors and publishers change. The shift of power from authors, publishers and/or content to the platform affects the development of new business models, and shaping the content in the digital environment becomes a major challenge for publishers. The subscription models of the content sale have long been present in other media industries. Editing, design and marketing are the key features that a publisher develops and adapts to changes. The traditional skills of publishers are no longer sufficient. Instead, a continued integration of innovative solutions is needed. The aim of this paper is to explore how the emergence of subscription models influences the development of new publishing products which bring together the author and the publisher in a joint effort to reach a larger number of readers.
Keywords: freemium; free content; business models; publishing; subscription